Nitrosilo complexos de rutênio : síntese, caracterização e avaliação de suas potencialidades citotóxicas - Golfeto, Camilla Calemi (2008)
The behavior of nitric oxide (NO) in biological systems has been under intense investigation in recent years in view of its possibly crucial role in a variety of physiological processes. Great progress in this area has been achieved by studying nitrosyl transition metal complexes. In this sense ruthenium complexes are by far the most studied and their relation to nitric oxide, acting as potential drugs, has been well explored in the literature. It should be punted out that ruthenium compounds normally exhibit fewer general toxicity problems than other metal-based drugs as showing by clinical experiments with a variety of ruthenium complexes, including some containing coordinated nitric oxide. Specifically for use as anticancer agents, ruthenium complexes are very promising, showing activity against tumors that have developed resistance to cisplatin or in which cisplatin is inactive. Nowadays two ruthenium-based anticancer drugs, NAMI-A [ImH][trans-RuCl4(DMSO)(Im)] and KP1019 [ImH][trans-RuCl4(Im)2] (Im = imidazole), have successfully completed phase I clinical trials and are scheduled to enter phase II trials in the near future. Also, the synthesis and evaluation of biological properties of ruthenium complexes with ligands of biological importance has attracted much attention of researchers of the bioinorganic area because the synergic effect from the ligand and metal residue can be expected once the administered coordination compound dissociates inside the body. Further beneficial effects can come from pharmaceutical principles based on coordination molecules, for example protection exerted by the metal-ligand bond against enzymatic degradation of the active ligand, modulation of hydrophobicity/hydrophilicity of the drug molecule and through this optimization of permeability of membranes. Thus these subjects have been performed in our laboratory and our research group has been interested in nitrosyl ruthenium complexes containing phosphine ligands, first to explore the structural, spectroscopic and electrochemical properties of such species with a focus on the effect of the type of isomer and co-ligands on the NO+ electronic characteristics. More recently was tested some of the compounds in cytotoxicity assays with a human tumor cell line, in order to evaluate their antitumor potential. Preliminary results were very promising and stimulate us to explore this potential in other nitrosyl ruthenium derivatives. In this work we report the preparation and characterization of nitrosyl complexes with the general formula cis-[RuCl2(NO)(dppp)(L)]PF6, where L is pyridine (py) [1], 4-Methylpyridine (4-Mepy) [2] or 4-Phenylpyridine (4-Phpy) [3] and dppp = 1,3-bis(diphenylphosphino)propane, obtained from the fac-[RuCl3(NO)(dppp)] precursor, and of nitrosyl complexes with the general formula cis-[RuCl(NO)(dppb)(N-N)](ClO4)2, where N-N is 2,2 -bipyridine (bipy) [4], 4,4 -dimethyl-2,2 -bipyridine (Me-bipy) [5],4,4 -dimethóxi-2,2 -bipyridine (MeO-bipy) [6], 4,4 -ichloro-2,2 -bipyridine (Cl-bipy)[7], e 1,10-phenantroline (fen) [8], and dppb = 1,4-bis(diphenylphosphino)butane. The preliminary cytotoxity activities against the MDA-MB-231 tumor cell line (human breast carcinoma) were tested for the compounds [1]-[3] and cis-[RuCl2(NO)(BPA)](HBPA=2-hydroxybenzyl-2-pyridylmethyl)amine, fac-[RuCl3NO(dppf)], RuCl3(NO).2H2O, the free ligands dppp and dppf and cisplatin, this last one for comparison with the new derived compounds. Cell viability was assayed by MTT reduction and the dose-survival curves obtained after 24 h drug treatment, showed a good activity with IC50 values of 21 ± 15; 7,4 ± 3,7; 7,1 ± 2,6; 87 ± 23 and 10 ± 3 μM for the complexes [1], [2], [3], respectively and cis-[RuCl2(NO)(BPA)] and fac-[RuCl3NO(dppf)].